AgriLOVE: Agriculture, land-use and technical change in an evolutionary, agent-based model - Matteo Coronese; Martina Occelli; Francesco Lamperti; Andrea Roventini (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2021)
This paper presents a novel agent-based model of land use and technological change in the agricultural sector under environmental boundaries, finite available resources and changing land productivity. In particular, we model a spatially explicit economy populated by boundedly-rational farmers competing and innovating to fulfill an exogenous demand for food, while coping with a changing environment shaped by their production choices. Given the strong technological and environmental uncertainty, farmers learn and adaptively employ heuristics which guide their decisions on engaging in innovation and imitation activities, hiring workers, acquiring new farms, deforesting virgin areas and abandoning unproductive lands. Such activities in turn impact on land productivity, food production, food prices and land use. We firstly show that the model can replicate key stylized facts of the agricultural sector. We then extensively explore its properties across several scenarios featuring different institutional and behavioral settings. Finally, we showcase the properties of model in different applications considering deforestation and land abandonment; soil degradation; and climate impacts.
Keywords: C63; Q15; Q16; Q50; Q55; 330; Agriculture; Land use; Agent-based model; Technological change; Environmental boundaries; Sustainability